The polyphenol (−)-epigallocatechin-3-gallate prevents apoA-IIowa amyloidosis in vitro and protects human embryonic kidney 293 cells against amyloid cytotoxicity. (2nd January 2016) - Nakajima, Hiroyuki; Nishitsuji, Kazuchika; Kawashima, Hiroyuki; Kuwabara, Kaori; Mikawa, Shiho; Uchimura, Kenji; Akaji, Kenichi; Kashiwada, Yoshiki; Kobayashi, Norihiro; Saito, Hiroyuki; Sakashita, Naomi
Abstract: Introduction : Apolipoprotein A-I (apoA-I) amyloidosis is either a non-hereditary form with deposits of wild-type apoA-I proteins in atherosclerotic plaques or a hereditary form with progressive accumulation of mutant apoA-I proteins in different tissues. Several small polyphenolic molecules reportedly inhibited formation of fibrillar assemblies of some amyloidogenic proteins and their cytotoxicity, but small molecules that inhibit apoA-I fibril formation have never been reported. Methods : Our methods included a thioflavin-T-binding assay, atomic force microscopy and dot blot and cell-based assays. Results : We showed that (−)-epigallocatechin-3-gallate (EGCG), a tea-derived flavanol, inhibited in vitro fibril formation and disaggregated fibrils preformed by the N-terminal 1–83 fragments of wild-type (WT) apoA-I and the G26R point mutation of apoA-I (apoA-IIowa ). We eliminated a common structure recognized by the anti-amyloid antibody OC by incubating apoA-IIowa with EGCG or treating apoA-IIowa fibrils with EGCG, which supported the above observation. In addition, EGCG rescued human embryonic kidney 293 cells from cytotoxicity and attenuated production of reactive oxygen species, which were induced by apoA-IIowa fibrils. Conclusions : Our results support the concept that EGCG inhibits amyloid fibril formation of various amyloidogenic proteins. Thus, EGCG may be a candidate for providing a structure to develop de novo inhibitors for amyloidosis treatment.